Malaysia's First Transplanted Case of Chronic Granulomatous Disease: The Journey of Overcoming Obstacles - Intan Hakimah Ismail; Faizah Mohamed Jamli; Ida Shahnaz Othman; Lokman Mohd Noh; Amir Hamzah Abdul Latiff (MDPI AG, 2016)
The awareness of primary immunodeficiency (PID) in Malaysia is still not forthcoming. Certain practical issues such as lack of clinical immunologists and specialized laboratory diagnostic facilities remain to be addressed. However, great efforts taken by passionate clinicians and scientists in the immunology networking have ascertained some prevalence. Despite the limitation, all suspected cases of PID are being properly investigated and competently managed. In this case report we highlighted the obstacles we faced in managing PID patients, particularly preparing for bone marrow transplant. This is the first transplanted case of chronic granulomatous disease in Malaysia, which emphasizes the importance of collaborative work to ensure further morbidities or mortalities are prevented.